EVALUATION OF PERFORMANCE APPRAISAL IN PT. XYZ - Tenges, Yuan Y.N (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Managing employee’s performance is imperative and it cannot be done if the employee’s potential and their ability to perform are not measured. Performance appraisal is a management tool that tries to count the employee’s performance. The term performance appraisal refers to the process by which an individual’s work performance is assessed. Research objective is to evaluate the performance appraisal in PT. XYZ. Performance appraisal is a process in which organizations evaluate or assess employee performance. Performance appraisals are employed to determine who needs what training, and who will be promoted, demoted, retained, or fired. Populations of this research are employee of PT X with 6 respondents.  Sample of this research is the employees of PT. XYZ in East Dumoga stock point. Result, the implementation of performance appraisal in PT. XYZ is goes well. It can be seen by employees’ positive perception. Although, performance appraisal in PT. XYZ still need some improvement to minimize possibility of error by giving employee a direct access to their performance appraisal result and develop a formal procedure in order to accommodate employee to appeal appraisal result that they consider inaccurate or unfair. Keywords: human resource management, performance appraisal